2017
DOI: 10.1016/j.etap.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing human metal accumulations in an urban superfund site

Abstract: Butte, Montana is part of the largest superfund site in the continental United States. Open-pit mining continues in close proximity to Butte’s urban population. This study seeks to establish baseline metal concentrations in the hair and blood of individuals living in Butte, MT and possible routes of exposure. Volunteers from Butte (n= 116) and Bozeman (n=86) were recruited to submit hair and blood samples and asked to complete a lifestyle survey. Elemental analysis of hair and blood samples was performed by IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…Data similar to ours and indicating the dependence of hair mineral composition (metabolic pool of chemical elements) of farm animals on the conditions of the biogeochemical province were obtained in other works [17][18][19][20][21]. There reports on a relationship between diet composition and the accumulation of chemical elements in body depots [22][23][24][25]. Data on the expressed link of the chemical elements metabolism with the horse's belonging to a genetically homogeneous group is in line with the results in laboratory animals [26].…”
Section: Elementsupporting
confidence: 82%
“…Data similar to ours and indicating the dependence of hair mineral composition (metabolic pool of chemical elements) of farm animals on the conditions of the biogeochemical province were obtained in other works [17][18][19][20][21]. There reports on a relationship between diet composition and the accumulation of chemical elements in body depots [22][23][24][25]. Data on the expressed link of the chemical elements metabolism with the horse's belonging to a genetically homogeneous group is in line with the results in laboratory animals [26].…”
Section: Elementsupporting
confidence: 82%
“…In contrast, some studies have reported elevated exposure and health burdens in the community. One pilot study comparing blood arsenic (As) levels in a sample population of Butte with a comparable sample in Bozeman, Montana, noted that Butte levels are statistically elevated [33]. Another study utilizing death certificate records found that in the period from 2006 to 2016, cancers, cerebral and cardiovascular diseases, and organ failures appeared to be elevated in Butte-Silver Bow County as compared to other counties in Montana [34].…”
Section: Study Areamentioning
confidence: 99%
“…Air monitoring for particulate matter (PM) was conducted at five locations throughout Butte over the same sampling period as residential soil and water (Figure 2). As previous research had indicated higher COC presence in larger aerosol size fractions [33], and other air monitoring results have found little-to-no COCs in the air when measured using total suspended particulate, coarse, and fine PM standards [27,38], an inhalable PM sampling method was employed. Each location utilized an Institute of Medicine (IOM) air sampler to collect the inhalable size fraction (50% cut point of 100 µm aerodynamic diameter) of ambient air PM (PM 100 ).…”
Section: Air Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 BEI set by ACGIH [54]. 6 US study control group median value [55]. 7 Median value for adults NHANES [56].…”
Section: Figurementioning
confidence: 99%